The possibility of practical application of behavioral economics theories for the service sector of the Russian Federation - G. A. Pozhilov (Путеводитель предпринимателя, 2021)
A necessary characteristic of economic science is its practical orientation in one way or another. With the development of the economy as a science, both the level and quality of life of people increases. Behavioral economics, being an interesting field of study and research, is actively integrated into the state and economic activities of foreign countries. In this article, it is proposed to study the possibility and limits of such integration in our country for the service sector.